2009
DOI: 10.1093/abbs/gmn017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LDL concentration polarization on the uptake of LDL by human endothelial cells and smooth muscle cells co-cultured

Abstract: To substantiate our hypothesis that concentration polarization of low-density lipoprotein (LDL) plays an important role in the localization of atherogenesis, we investigated the effects of wall shear stress and water filtration rate (or perfusion pressure) on the luminal surface LDL concentration (c w ) and the LDL uptake by human vascular endothelial cells and smooth muscle cells co-cultured on a permeable membrane using a parallel-plate flow chamber technique and a flow cytometry method. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Lipoprotein concentration polarization and flow field changes appear to lead to the alteration of atherogenic lipid transportation across the arterial luminal surface, causing vascular diseases such as lipoprotein deposition, blood platelet accumulation and intima thickening. Previous in vitro studies have shown that LDL concentration polarization exists in the vascular system [17][18][19][20][33][34][35][36]. In our study, the transparent segment of the rabbit carotid artery was vertically scanned along the z-axis using the computed tomography scanning capability of LSCM.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein concentration polarization and flow field changes appear to lead to the alteration of atherogenic lipid transportation across the arterial luminal surface, causing vascular diseases such as lipoprotein deposition, blood platelet accumulation and intima thickening. Previous in vitro studies have shown that LDL concentration polarization exists in the vascular system [17][18][19][20][33][34][35][36]. In our study, the transparent segment of the rabbit carotid artery was vertically scanned along the z-axis using the computed tomography scanning capability of LSCM.…”
Section: Discussionmentioning
confidence: 99%
“…Ox-LDL is believed to play a key role in cellular dysfunction, as well as cholesterol accumulation and subsequent foam-cell transformation in macrophages and SMCs [12][13][14][15][16][17][18][19][20][21][22][23][24]. Because the endothelium of the artery displays low permeability to plasma proteins, it has been suggested that the filtration flow across the artery wall may cause concentration polarization of LDLs with the LDLs increasing in concentration from bulk value towards interface within the arterial system [8].…”
Section: Discussionmentioning
confidence: 99%
“…The same experimental perfusion system as the one described previously by Ding et al [20] was used in the present study ( figure 1). It consisted of a head tank, a downstream collecting reservoir, a modified parallelplate flow chamber with a height of 0.5 Â 10 23 m, a peristaltic flow pump to circulate the perfusion fluid (DMEM) and a blender of air and CO 2 with a constant temperature (378C + 18C).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…With increasing LDL concentration, shear stress increases LDL uptake by human ECs when co-cultured with VSMCs [140]. Shear stress inhibits VSMC-induced inflammatory gene expression in ECs [141].…”
mentioning
confidence: 99%